Problems Of Modernization Of Professional Preparation Of The Students Of Pedagogical Higher Education Institutions - Asatryan, Zaruhi; Asatryan, Margarit (Զանգակ հրատ.)
The article touches upon the problems of modernizing the professional preparation of the students of pedagogical Higher Education Institutions (HEIs). It proves that the deepening of market relations and the contemporary level of the development of public life put great demands on the HEIs in terms of preparing highly qualified specialists. Due to the socio-economic transformations, it is required that the entire education system of pedagogical HEIs should be reformed and a new graduate model should be elaborated. Among the significant problems, the authors single out the modernization of the system of the specialist preparation, the elaboration of new integrated educational strategies, models and technologies for the development of higher education systems, mutual understanding and collaboration among various education systems. Therefore the issues of the future specialists’ professional competency, reflective teaching/learning, the development of meta-competences, competitiveness and media literacy come to the fore. The solution to these problems implies a change in the requirements of the HEI graduate model, approaches and expected outcomes. The problem of developing a new methodology for the preparation of specialists in pedagogy at HEIs and improving the quality of the professional preparation should be considered in terms of functional, systematic, cultural, competence and anthropological approaches. The article provides justification for the claim that the process of the future pedagogues’ professional preparation should be regarded as the integrity of interrelated structural components, including the aim, content, management, operation, outcome. The effectiveness of the professional preparation at contemporary pedagogical HEIs is conditioned by certain managerial functions, principles, methods, implementation of innovations into the management of the higher education policy and the modernization of the content of the graduate model. The article presents social pedagogical conditions for the effective preparation of the HEI students and highlights a number of factors that contribute to the effectiveness of this process.
Keywords: Pedagogy